The Scavenger Receptor SSc5D Physically Interacts with Bacteria through the SRCR-Containing N-Terminal Domain - Bessa Pereira, Catarina; Bocková, Markéta; Santos, Rita F.; Santos, Ana Mafalda; Martins de Araújo, Mafalda; Oliveira, Liliana; Homola, Jiří; Carmo, Alexandre M. (Frontiers in Immunology, 2016)
The scavenger receptor cysteine-rich (SRCR) family comprises a group of membrane-attached or secreted proteins that contain one or more modules/domains structurally similar to the membrane distal domain of type I macrophage scavenger receptor. Although no all-inclusive biological function has been ascribed to the SRCR family, some of these receptors have been shown to recognize pathogen-associated molecular patterns (PAMP) of bacteria, fungi or other microbes. SSc5D is a recently described soluble SRCR receptor produced by monocytes/macrophages and T lymphocytes, consisting of an N-terminal portion which contains five SRCR modules, and a large C-terminal mucin-like domain. Towards establishing a global common role for SRCR domains, we interrogated whether the set of five SRCR domains of SSc5D displayed pattern recognition receptor (PRR) properties. For that purpose, we have expressed in a mammalian expression system the N-terminal SRCR-containing moiety of SSC5D (N-SSc5D), thus excluding the mucin-like domain likely by nature to bind microorganisms, and tested the capacity of the SRCR functional groups to physically interact with bacteria. Using conventional protein-bacteria binding assays, we showed that N-SSc5D had a superior capacity to bind to E. coli strains RS218 and IHE3034 compared with that of the extracellular domains of the SRCR proteins CD5 and CD6 (sCD5 and sCD6, respectively), and similar E. coli-binding properties as Spα, a proven PRR of the SRCR family. We have further designed a more sensitive, real-time and label-free surface plasmon resonance (SPR)-based assay, and examined the capacity of N-SSc5D, Spα, sCD5 and sCD6 to bind to different bacteria. We demonstrated that the N-SSc5D compares with Spα in the capacity to bind to E. coli and L. monocytogenes, and further that it can distinguish between pathogenic E. coli RS218 and IHE3034 strains and the non-pathogenic laboratory E. coli strain BL21(DE3). Our work thus advocates the utility of SPR-based assays as sensitive tools for the rapid screening of interactions between immune-related receptors and PAMP-bearing microbes. The analysis of our results suggest that SRCR domains of different members of the family have a differential capacity to interact with bacteria, and further that the same receptor can discriminate between different bacteria strains and species.